Actores y discursos religiosos en la protesta social - Pérez, Rolando (Pontificia Universidad Católica del Perú. Fondo Editorial, 2015)
This article analyses the roles played by the actors related to religious groups,the way that they rebuild their participation and representation in the publicspace from their involvement in the initiative of social protest about the reclaimand defense of certain civil rights. In this regard, the article addresses the relationship between religion and politics, and furthermore specifically, the way inwhich religious human capital contributes to the process of collective actionsand social mobilization. At the same time, it offers some ideas regarding theway in which religious speech and public practice is shaped by cultural mediatization.

Este artículo analiza los roles que juegan los actores vinculados a los gruposreligiosos y cómo reconstruyen su participación y representación en el espaciopúblico a partir de su involucramiento en iniciativas de protesta social por lareivindicación y defensa de determinados derechos. En este sentido, reflexionaen torno a la relación entre lo religioso y lo político, y más específicamente,el modo como el capital religioso aporta en estos procesos de acción colectivay movilización social, pero al mismo tiempo el modo como el discurso y lapráctica pública religiosa es moldeada por los procesos de mediatización dela cultura.
Keywords: Capital religioso; Protesta social; https://purl.org/pe-repo/ocde/ford#5.09.01